THE IMPLEMENTATION OF THE FUNCTIONS OF SPECIAL DEVELOPMENT INSTITUTIONS FOR CHILDREN IN THE PROTECTION OF HUMAN RIGHTS FOR CHILDREN - Sari, Andi Rima Febrina; Razak, Abdul; Muchtar, Syamsuddin (Tadulako Law Review, 2020)
Criminal or criminal conduct is carried out in a Penitentiary through guidance and guidance given to those who have broken the law. This fostering policy with the Penitentiary System reflects that the State of Indonesia is a country that upholds Human Rights. The aim of this research is to find out the forms of fulfillment of human rights for children who commit crimes in the Special Guidance Institution of Children and the prospects for the implementation of the functions of the Special Guidance Institution of Children in protecting human rights for children. This research is empirical normative legal research. Based on normative jurisprudence and seeing the facts directly in the field relating to the form of coaching conducted in Special Child Development Institute Class II Parepare. The results of the study showed that basically the forms of education, skills training, and personality development that have been carried out in Special Child Development Institute Class II Parepare but are considered not yet optimal in fulfilling human rights for children and have not proceeded properly. The protection of human rights for children where in order to be able to realize the concept of child development in the Special Child Development Institute in accordance with the fulfillment of human rights for children needs to change the mindset or mindset of the goal of child punishment, shifting thinking from punishment to punishment coaching for children, besides the need for cooperation that can not be separated from coordination between institutions, both the Ministry of Law and Human Rights, the Ministry of Social Affairs, the Ministry of Education, the Ministry of Women's and Child Empowerment, the Indonesian Child Protection Commission, Non-Governmental Organizations, Foundations and Institutions other institutions involved in implementing child development in accordance with Law Number 11 of 2012 concerning the Juvenile Criminal System.